Bovine leukemia virus occurrence in Dagestan - N. R. Budulov; M. M. Mikailov; Sh. A. Gunashev; E. A. Yanikova; A. A. Halikov (Ветеринария сегодня)
Results of diagnostic tests for bovine leukosis carried out in the Dagestan Republic in 2022 (as of October 1, 2022) showing bovine leukemia virus (BLV) occurrence are presented in the paper for the whole Republic and for each municipality separately. In total, 632,454 susceptible animals were serologically tested with immunodiffusion assay; 3,573 reactor animals (0.6% of tested animals) were detected. Proportion of infected animals was as follows: 0.5% – in administrative raions, 1.6% – in urban districts and 1.1% – in distant pasture zones. Percentage of infected cattle varied from 0.01 to 4.9%. No hematological examinations for bovine leukosis were carried out because seropositive animals were timely culled. In the breeding sector, the proportion of bovine leukemia virus carriers was averagely 2.8%. Ninety-five bovine leukosis-affected localities were reported in the region as of 1 January 2022. Eighty-one new BLV-infected localities had been identified and bovine leukosis had been eliminated in 18 localities for 9 months of 2022. Totally, 158 localities were officially declared affected in 2022 (as of October 1, 2022): 36 agricultural holdings (including 5 breeding holdings), 18 small-scale farms and 104 backyard farms. The largest number of bovine leukosis-affected localities was registered in the Kizlyarsky (18), Tarumovsky (17), Babayurtovsky (16), Gunibsky (15), Tlyaratinsky (10) Raions and in the city of Makhachkala (9). One disease-affected locality was reported in each of the Bezhtinsky, Buynaksky, Derbentsky, Kazbekovsky, Kayakentsky, Kizilyurtovsky, Khasavyurtovsky Raions and towns of Khasavyurt and Yuzhno-Sukhokumsk. Two disease-affected localities were reported in each of the Rutulsky, Untsukulsky Raions, three disease-affected localities were reported in each of the Gergebilsky, Laksky, Novolaksky, Tsumadinsky Raions. Four disease-affected localities were reported in the Sergokalinsky Raion, five disease-affected localities were reported in the Charodinsky Raion, six disease-affected localities were reported in each of the Akhvakhsky, Dakhadaevsky, Karabudakhkentsky Raions, seven disease-affected localities were reported in each of the Botlikhsky, Kumtorkalinsky and Shamilsky Raions. Comparative analysis of serological and molecular genetic methods used for bovine leukosis diagnosis demonstrated the advantage of enzyme-linked immunosorbent assay and polymerase chain reaction as compared to immunodiffusion assay used in veterinary practice.